2010
DOI: 10.1158/0008-5472.can-09-2670
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Proliferation and Antiapoptosis Driven in Breast Cancer Stem Cells by Stem Cell Protein Piwil2

Abstract: Cancer stem cell studies may improve understanding of tumor pathophysiology and identify more effective strategies for cancer treatment. In a variety of organisms, Piwil2 has been implicated in multiple roles including stem cell self-renewal, RNA silencing, and translational control. In this study, we documented specific expression of the stem cell protein Piwil2 in breast cancer with predominant expression in breast cancer stem cells. In patients who were evaluated, we determined that 90% of invasive carcinom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 30 publications
7
85
0
Order By: Relevance
“…Recently, more and more pieces of evidence have confirmed that Piwil2 is expressed in various tumors or cancer cell lines, playing important roles in tumorigenesis and protecting cells from apoptosis (11,14,36). Our previous results also indicate that Piwil2 inhibits apoptosis through TGF-␤ signaling in HEK293 cells and suppresses p53 in tumor cells (12,13).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Recently, more and more pieces of evidence have confirmed that Piwil2 is expressed in various tumors or cancer cell lines, playing important roles in tumorigenesis and protecting cells from apoptosis (11,14,36). Our previous results also indicate that Piwil2 inhibits apoptosis through TGF-␤ signaling in HEK293 cells and suppresses p53 in tumor cells (12,13).…”
Section: Discussionsupporting
confidence: 54%
“…Our previous work showed that human Piwil2 inhibits apoptosis by regulating the transforming growth factor beta (TGF-␤) pathway in HEK293 cells and the STAT3/p53 pathway in tumor cells (12,13). Furthermore, Piwil2 also exhibited resistance in response to other forms of stimuli to apoptosis (14)(15)(16).…”
mentioning
confidence: 99%
“…A similar trend was evident when colony formation assay was Furthermore, we compared the estrogen/ER gene signature with miR-191 signature and identified 51 genes that were commonly regulated ( Figure 6D (25,36-38)). We confirmed transcript levels of few genes known to promote E2/ER-mediated cell proliferation-ESR1, ESR2, piwi-like 2, PLAC1 and AnxA1 (35,36,39,40). Estrogen treatment of MCF7 cells mediated induction of these genes that was reversed by treatment with estrogen antagonist (Tm) ( Figure 6E).…”
Section: Estrogen-mediated Cellular Proliferation Is Mir-191 Dependentsupporting
confidence: 60%
“…Very recently, the hiwi gene was also reported to promote the growth of human breast tumors [46], gastric tumors [40], and hepatocellular carcinoma cells [72]. The piwil2 gene was suggested to modulate the proliferation of colon cancer [58] and breast cancer [51,53]. In Drosophila, PIWI and AUB were demonstrated to contribute to the growth of malignant brain tumors [79].…”
Section: Piwis Are Involved In Promoting Cell Proliferationmentioning
confidence: 99%